Contribution of the A. baumannii A1S_0114 Gene to the Interaction with Eukaryotic Cells and Virulence - Rumbo-Feal, Soraya; Pérez, Astrid; Ramelot, Theresa A.; Álvarez-Fraga, Laura; Vallejo, Juan A.; Beceiro, Alejandro; Ohneck, Emily J.; Arivett, Brock A.; Merino, María; Fiester, Steven E.; Kennedy, Michael A.; Actis, Luis A.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Genetic and functional studies showed that some components of the Acinetobacter baumannii ATCC 17978 A1S_0112-A1S_0119 gene cluster are critical for biofilm biogenesis and surface motility. Recently, our group has shown that the A1S_0114 gene was involved in biofilm formation, a process related with pathogenesis. Confirming our previous results, microscopy images revealed that the ATCC 17978 Δ0114 derivative lacking this gene was unable to form a mature biofilm structure. Therefore, other bacterial phenotypes were analyzed to determine the role of this gene in the pathogenicity of A. baumannii ATCC 17978. The interaction of the ATCC 17978 parental strain and the Δ0114 mutant with A549 human alveolar epithelial cells was quantified revealing that the A1S_0114 gene was necessary for proper attachment to A549 cells. This dependency correlates with the negative effect of the A1S_0114 deletion on the expression of genes coding for surface proteins and pili-assembly systems, which are known to play a role in adhesion. Three different experimental animal models, including vertebrate and invertebrate hosts, confirmed the role of the A1S_0114 gene in virulence. All of the experimental infection assays indicated that the virulence of the ATCC 17978 was significantly reduced when this gene was inactivated. Finally, we discovered that the A1S_0114 gene was involved in the production of a small lipopeptide-like compound herein referred to as acinetin 505 (Ac-505). Ac-505 was isolated from ATCC 17978 spent media and its chemical structure was interpreted by mass spectrometry. Overall, our observations provide novel information on the role of the A1S_0114 gene in A. baumannii’s pathobiology and lay the foundation for future work to determine the mechanisms by which Ac-505, or possibly an Ac-505 precursor, could execute critical functions as a secondary metabolite.